Comparing the Prognostic Value of Lactate to the Neutrophil to Lymphocyte Ratio Among Sepsis Patients: A Prospective Cohort Study - Bou Chebl R; Haidar S; Kattouf N; Assaf M; Alwan JS; Khamis MM; Abdeldaem K; Makki M; Tamim H; Abou Dagher G (Open Access Emergency Medicine)
Ralphe Bou Chebl,1,* Saadeddine Haidar,1,* Nadim Kattouf,1 Mohamad Assaf,1 Joudie Sahar Alwan,1 Mohamad Moustafa Khamis,1 Karim Abdeldaem,1 Maha Makki,2 Hani Tamim,2 Gilbert Abou Dagher1 1Department of Emergency Medicine, American University of Beirut, Beirut, Lebanon; 2Department of Internal Medicine, American University of Beirut, Beirut, Lebanon*These authors contributed equally to this workCorrespondence: Gilbert Abou Dagher, Associate Professor of Clinical Emergency Medicine, Department of Emergency Medicine, American University of Beirut Medical Center, P.O.Box - 11-0236, Riad El Solh, Beirut, 1107 2020, Lebanon, Tel +961 1 350000 Ext: 6631, Email ga66@aub.edu.lbBackground: Lactate has long been recognized as a key prognostic biomarker in sepsis. Similarly, the prognostic role of the neutrophil-to-lymphocyte ratio (NLR) has been investigated in various conditions, including sepsis. Previous studies have explored the optimal NLR cutoff to differentiate sepsis survivors from nonsurvivors, predict bacteremia, diagnose sepsis, and assess mortality. This study compares the prognostic value of lactate and NLR in septic patients.Methods: This prospective cohort study included 874 adult septic or septic shock patients presenting to a tertiary care center’s Emergency Department between September 2018 and February 2021. The primary outcome was to compare the prognostic value of NLR and lactate regarding in-hospital mortality. Secondary outcomes compared their prognostic value in different septic subgroups.Results: Stepwise logistic regression showed NLR was not associated with in-hospital mortality (OR=1.003, p=0.544), while lactate was significantly associated with in-hospital mortality (OR=1.188, p< 0.0001). There was no significant difference in the AUCs of NLR and lactate (0.552 vs 0.591, p=0.22). Lactate outperformed NLR in patients with albumin < 30, those < 65 years old, and those with sepsis from a urinary tract infection. No significant differences were found in AUCs between lactate and NLR in patients with septic shock, Lactate< 2, Lactate≥ 2, diabetes, malignancy, chronic kidney diseases, other sources of infection, albumin ≥ 30 and age ≥ 65.Conclusion: In this study, lactate but not NLR was associated with in-hospital mortality. There was no significant difference in the AUCs between lactate and NLR among sepsis patients and among most of the subgroups. However, lactate outperformed NLR in the following subgroups: albumin< 30 g/L, patients < 65 years old and patients with sepsis due to a urinary tract infection. Our results advocate for the continued use of serum lactate rather than NLR, despite its limitations, as a predictor of mortality among septic patients and the different subgroups in this study.Keywords: sepsis, septic shock, lactate, mortality, neutrophil to lymphocyte ratio, prognosis